Novel delivery of cellular therapy to reduce ischemia reperfusion injury in kidney transplantation. Issue 4 (28th June 2020) - Thompson, Emily R.; Bates, Lucy; Ibrahim, Ibrahim K.; Sewpaul, Avinash; Stenberg, Ben; McNeill, Andrew; Figueiredo, Rodrigo; Girdlestone, Tom; Wilkins, Georgina C.; Wang, Lu; Tingle, Samuel J.; Scott, William E.; et al.
Abstract : Ex vivo normothermic machine perfusion (NMP) of donor kidneys prior to transplantation provides a platform for direct delivery of cellular therapeutics to optimize organ quality prior to transplantation. Multipotent Adult Progenitor Cells (MAPC ® ) possess potent immunomodulatory properties that could minimize ischemia reperfusion injury. We investigated the potential capability of MAPC cells in kidney NMP. Pairs (5) of human kidneys, from the same donor, were simultaneously perfused for 7 hours. Kidneys were randomly allocated to receive MAPC treatment or control. Serial samples of perfusate, urine, and tissue biopsies were taken for comparison. MAPC‐treated kidneys demonstrated improved urine output ( P = .009), decreased expression of injury biomarker NGAL ( P = .012), improved microvascular perfusion on contrast‐enhanced ultrasound (cortex P = .019, medulla P = .001), downregulation of interleukin (IL)‐1β ( P = .050), and upregulation of IL‐10 ( P < .047) and Indolamine‐2, 3‐dioxygenase ( P = .050). A chemotaxis model demonstrated decreased neutrophil recruitment when stimulated with perfusate from MAPC‐treated kidneys ( P < .001). Immunofluorescence revealed prelabeled MAPC cells in the perivascular space of kidneys during NMP. We report the first successful delivery of cellular therapy to a human kidney during NMP. Kidneys treated with MAPC cells demonstrate improvement in clinically relevant parameters and injury biomarkers. This novel method of cell therapy delivery provides an exciting opportunity to recondition organs prior to transplantation. Abstract : Ex vivo reconditioning of human kidneys by delivery of multipotent adult progenitor cells during normothermic machine perfusion reduces ischemia reperfusion injury. Steichen and Erpicum's editorial is on page 1359 .